STRATEGI PENGEMBANGAN AKTIVITAS WISATA DI OBJEK WISATA IKAN SAKTI SUNGAI JANIAH KABUPATEN AGAM - Randi Hidayat; Yuliana Yuliana; Hijriyantomi Suyuthie (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
This research aims to formulate a development strategy that consists of strengths, weaknesses, opportunities and threats of tourism activities in the tourism object Ikan Sakti Sungai Janiah. This research is a descriptive research with qualitative data. Data collection techniques in this research were conducted by using the method of interviewing, observation and documentation involving several informants by using purposive sampling technique. The results of this study indicate that: 1) The strength of the development of tourism activities in the tourism object Ikan Sakti Sungai Janiah is the existence of a supportive land, there has been a conscious group of tourism, beautiful atmosphere and uniqueness of tourist attractions and traditions that are not owned by other regions. 2) The weakness of the development of tourism activities in the tourism object Ikan Sakti Sungai Janiah is the land that still belongs to the community, not regular art and cultural events, the security of tourists wich are not guaranteed and the lack of capital and community skills. 3) Opportunities from the development of tourism activities in the tourism object Ikan Sakti Sungai Janiah is the availability of new employment opportunities for the community, adding tourist attractions supporting facilities, the cooperation between various agencies, and the emergence of groups that support tourism activities. 4) The threat of tourism activity in the tourism object Ikan Sakti Sungai Janiah is the increasing of waste, the destruction of the environment, the emergence of groups that disturb the security of tourists, and illegal traders. Strategy of development of tourism activity in the tourism object Ikan Sakti Sungai Janiah is a) to maximize the surrounding potential of land and human resources, b) cooperate with various institutions and community, c) optimize the participation of various circles related to tourism activities, d) adding supporting facilities for the smoothness of tourism activities.